중국 고교 교육과정 및 대학입시 변화에 따른 경제 교육에 대한 영향 연구 - 김동하(Kim Dong-Ha) (中國學, 2024)
시진핑 신정부가 2013년에 들어서면서 교육부는 정치교육을 강화하였다. 교육부는 고교학업수평고사 도입(2014), 대학입시제도 개혁(2016), 고교교육과정표준 개혁(2017 /2020)을 진행했는데, 그 결과 고교 경제교육 체계와 내용은 다음과 같이 변화되었 다. 첫째, 경제영역을 포함한 ‘사상정치’는 선택성 과목으로 바뀌었다. 둘째, 사상정치 중 정치영역 학습량은 늘어난 반면, 경제영역은 감소 되었다. 셋째, 영미권 ’주류경제 학‘의 주요 개념과 이론교육이 생략되었다. 넷째, 대학입시 선택과목 중 사상정치가 선택되는 비율이 최저치로 떨어졌다. 다섯째, 사상정치 중 경제영역 문제 비중은 2 4% 수준으로 축소되었고, 난이도는 더 쉬워졌다. 여섯째, 정치교육 강화 방침에 따라 사상정치 교과목의 절대 학습량은 오히려 증가했다. As the new Xi Jinping administration entered 2013, the Ministry of Education strengthened political education. The Ministry of Education introduced the high school academic evaluation test (2014), the university entrance examination system reform (2016), and the high school curriculum standard reform (2017/2020), as a result, the high school economic education system and contents were changed as follows. First, ‘Thought Politics’, including the economic field, was changed to an optional subject. Second, among the ‘Thought Politics’, the amount of learning in the political field increased, while the economic field decreased. Third, the main concepts and theoretical education of mainstream Western economics were omitted. Fourth, the proportion of selecting ‘Thought Politics’ among the elective subjects for college entrance exams fell to the lowest level. Fifth, the proportion of questions in the economic field among the ‘Thought Politics’ was reduced to 24%, and the difficulty became easier. Sixth, the absolute amount of learning in ‘Thought Politics’ subjects increased according to the policy to strengthen political education.